The Effectiveness and Trust of Students Using Sharia Fintech Applications in Paying Tuition Fees at the Rokan Islamic Institute - Ahmad Arifin; Fery Sudarmanto; Lailatul Husna; Dedek Sri Wahyuni; M Kamal Hadi (Jurnal Kawakib, 2025)
The purpose of this study is to determine: 1) Student confidence in using the Sharia Fintech application in making tuition payment transactions at the Rokan Islamic Institute from a Sharia Economic Perspective; 2) Student effectiveness in using the Sharia Fintech application in making tuition payment transactions at the Rokan Islamic Institute from a Sharia Economic Perspective.This type of research is qualitative research. The informants were 7 people. Data collection techniques used were interviews, observation, and questionnaire documentation. Data analysis techniques used were data reduction, data presentation, and verification (drawing conclusions). The results of this study are as follows:1) Students' trust in using the Sharia Fintech application in making tuition payment transactions at the Islamic Institute of Rokan from a Sharia Economic Perspective is high, meaning students feel the system is safe, reliable, and in accordance with sharia economic principles, thus increasing their confidence in conducting digital transactions. This trust is strengthened by personal data protection, transaction transparency, and the bank's commitment to customers, all of which are in accordance with sharia principles; 2) Students' effectiveness in using the Sharia Fintech application in making tuition payment transactions at the Islamic Institute of Rokan from a Sharia Economic Perspective is considered effective. This application makes it easier for students to access services, speeds up the transaction process, provides appropriate information, and has complete features that support user convenience. This effectiveness is also in line with sharia economic principles, so students can conduct transactions safely, efficiently, and in accordance with sharia